Influence of electrode erosion on formation of long-living luminous objects, formed by electrical discharge in water - Golubnichy, P.I.; Krutov, Yu.M.; Nikitin, E.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
This paper presents the results of experimental studies of the influence of electrode erosion, which occurs during the electrical discharge in liquid on formation of long-living luminous objects. On the basis of these results the authors conclude that the electrode material is not only involved in the formation of long-living luminous objects, but also hinders this formation. Представлены результаты экспериментальных исследований влияния эрозии электродов, которая происходит во время электрического разряда в жидкости, на процесс формирования долгоживущих светящихся объектов. На основе полученных данных авторы делают вывод о том, что материал электродов не только не участвует в процессе формирования долгоживущих светящихся объектов, но и препятствует их образованию. Представлені результати експериментальних досліджень впливу ерозії електродів, яка відбувається під час електричного розряду у рідині, на процес формування довгоіснуючих світних об'єктів. На основі отриманих даних автори роблять висновок про те, що матеріал електродів не тільки не бере участі у процесі формування довгоіснуючих світних об'єктів, але і перешкоджає їх утворенню.